Quantum Confinement and Gas Sensing of Mechanically Exfoliated GaSe. Issue 1 (7th November 2016) - Wu, Yecun; Zhang, Duan; Lee, Kangho; Duesberg, Georg S.; Syrlybekov, Askar; Liu, Xiao; Abid, Mourad; Abid, Mohamed; Liu, Yanqi; Zhang, Lisheng; Coileáin, Cormac Ó; Xu, Hongjun; et al.
Abstract : GaSe layers with thicknesses ranging from a monolayer to 100 nm are successfully mechanically exfoliated for use in gas sensing. In combination with density functional theory calculations, general guidelines to determine the number of layers using Raman spectra are presented. With decreasing layer numbers, quantum confinement induces a red‐shift for out‐of‐plane modes and a blue‐shift for in‐plane modes. The relative Raman shifts of the out‐of‐plane vibrational modes A ′ 1 ( 1 1 ) and A ′ 1 ( 2 2 ) grow exponentially with decreasing stack thickness from 100 to 1 layers. Moreover, the change in first‐order temperature coefficient (χ) also increases exponentially as the number of layers is reduced, with the value of the first‐order temperature coefficient of the A ′ 1 ( 2 2 ) mode of monolayer GaSe (≈−1.99 × 10 −2 cm −1 K −1 ) being almost double that of 100 layer GaSe (≈−1.22 × 10 −2 cm −1 K −1 ). Finally, the exfoliated GaSe is used for gas sensing and shows high sensitivity, displaying a minimum detection limit of 4 ppm for NH3 at room temperature, confirming the potential of mechanically exfoliated GaSe in high‐sensitivity gas sensors. Abstract : GaSe, a layered semiconductor, is attractive for electronic and optoelectronic applications. Here, GaSe layers with thicknesses ranging from a monolayer to 100 nm are successfully mechanically exfoliated for use in gas sensing. General guidelines to rapidly determine the number of layers are presented and high‐sensitivity gas sensors based on exfoliated GaSe are also demonstrated.